Subjective depressive symptoms associated with pain in patients with major depressive disorder: Findings from the study on the aspect of Asian depression - Awirut Oon-Arom (2019)
© 2019 Wiley Periodicals, Inc. Purpose: To examine subjective depressive symptoms associated with physical pain symptoms (PPSs) in Asian patients with major depressive disorder (MDD). Design and methods: Four PPSs, including headache, chest pain, low back pain, and muscle pain, and subjective depressive symptoms were assessed using the Symptom Checklist-90-Revised. Findings: Out of 528 participants, 390 (73.9%) had at least one PPS. After adjusting for sex, depression severity, disability, fatigue, physical health status, and mental health status, PPSs were found to be associated with crying easily, blaming oneself, feeling lonely, feeling blue, and worrying too much. Practical implications: Almost three-quarters of Asian patients with MDD experience PPSs. PPSs are associated with some subjective feelings of depression.